Primary Spinal Syringomyelia with Hemianhidrosis: A Rare Case Report - Dwi Fitria Nova; Dian Ayu Hamama Pitra (Sumatera Medical Journal, 2025)
Background: The incidence of syringomyelia is very rare, at 8.4 per 100,000 people, or about 2%. It is characterized by a cyst filled with cerebrospinal fluid (CSF) within the spinal cord tissue or central canal. Symptoms may include sensory and motor disturbances. Objective: We report a case of a 35-year-old woman who presented with pain, weakness, and stiffness in her back, shoulders, arms, and legs. Methods: She experienced weakness on her right side for the past five years and had no sweating on that side for two years. Motor examination showed flaccid hemiparesis and muscle atrophy in her right upper limb. Reflex testing revealed hyperreflexia in her right hand and leg. Sensory testing (touch, temperature, pain, vibration) showed dissociation of sensation on the medial-lateral side of her right arm and leg. Results: After 1.5 years of treatment, including routine Short Wave Diathermy (SWD), Transcutaneous Electrical Nerve Stimulation (TENS), physical therapy, and medication, her condition improved, and her quality of life was enhanced. Conclusion: This case highlights that a multidisciplinary approach, including SWD, TENS, physical therapy, and medication, can effectively reduce symptoms and improve quality of life in syringomyelia patients, even with extensive spinal involvement (C1-T11).